84.4k views
9 votes
A student solved the equation 3(–4 + x) – 5x = 7x + 15. Find her mistake and correct it.

User Eroomydna
by
4.8k points

1 Answer

13 votes
your answer is x = -3 !!

step 1.) distribute 3 through the parentheses
-12+3x-5x = 7x+15

step 2.) collect like terms
-12-2x = 7x+15

step 3.) move the variable to the left-hand side and change its sign
-2x-7x = 15+12

step 4.) collect like terms
-9x = 15+12

step 5.) add the numbers
-9x = 27

step 6.) divide both sides of the equation by -9

so x would equal -3 !! :D
User Searles
by
5.2k points